A Real-Time Assessment of Aquatic Ecological Health Using a Process-Based Model: An Example From Lake Poyang, China - Qi, Lingyan; Xiong, Ailing; Wu, Fengwen; Gao, Junfeng; Jia, Cai; Zhi, Junjun; Liu, Wangbing; Wang, Jian; Hou, Changli; Zhang, Lin; Xu, Bing (Frontiers in Environmental Science, 2022)
Aquatic ecological health is a global challenge due to its significant impacts, and a real-time method to accurately assess ecological health is therefore particularly useful. Based on the hydrological, water quality, meteorological, and topographic data collected from field observations and organizations, this study developed a process-based hydrodynamic and water quality model using an environmental fluid dynamics code (EFDC) model of Lake Poyang to simulate the spatiotemporal variations in water levels, and the total nitrogen (TN), total phosphorus (TP), and chlorophyll a (Chl a) contents. Compared with the measured values, the models were confirmed to be reliable and acceptable. Then, to achieve a real-time assessment, the simulated results were calculated and transformed to five ordinal rating categories by using a lake ecosystem health assessment framework. Our research revealed the following results: (1) the highest and lowest 10-day water level statuses indicated that the hydrological conditions of this lake were at “good” or “excellent” levels. (2) The health levels of TN were mostly at the “fair” level or below, and most of the real-time assessment health curves of lake zones were close to the single peak type. (3) The TP contents were often at “good” levels, and the health assessment curves of the lake zones exhibited downwards trends during the periods of rapid rise or retreat. (4) A fluctuating characteries was found in the health assessment of Chl a, with at least two declining peaks in all lake zones. This study demonstrated the high value of physics-based models for assessing the ecological health of aquatic ecosystems in a robust and accurate manner.